Comparison of anti-SARS-CoV-2 IgG seropositivity among vaccinated, unvaccinated, and COVID-19 survivor individuals: A cross-sectional study in Palembang, Indonesia - Retnaningsih, Ekowati; Nuryanto, Nuryanto; Oktarina, Reni; Komalasari, Oom; Maryani, Sri; Larasti, Veny; Fertilita, Soilia (Narra J, 2025)
Measurement of anti–severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobulin G (IgG) antibody levels provides evidence of prior infection or vaccination. Persistent vaccine hesitancy underscores the importance of robust, evidence-based data to inform policy decisions. The aim of this study was to compare anti-SARS-CoV-2 IgG seropositivity among vaccinated individuals, unvaccinated individuals, and coronavirus disease 2019 (COVID-19) survivors in the community during the pandemic. In this cross-sectional study, 517 participants were enrolled, including 167 vaccinated individuals, 97 COVID-19 survivors, and 253 unvaccinated individuals, selected through multistage cluster sampling of 40 clusters. Anti-SARS-CoV-2 IgG seropositivity was defined as ≥50 AU/mL. Multivariable logistic regression was performed to evaluate associations between group type and seropositivity, adjusting for demographic factors, COVID-19 symptoms, hypertension, and body mass index (BMI). Vaccinated individuals demonstrated significantly higher odds of seropositivity compared with unvaccinated participants (odds ratio (OR)=5.60; 95% confidence interval (CI): 2.36–13.27). Covariates independently associated with seropositivity (p<0.05) included the presence of COVID-19 symptoms, hypertension, and BMI. Vaccination was strongly associated with increased anti-SARS-CoV-2 IgG seropositivity in the community, independent of clinical and demographic factors. These findings support ongoing vaccination campaigns and highlight the relevance of comorbidities and symptomatic history in shaping humoral immune responses.